Meditation and neurodegenerative diseases. (7th August 2013) - Newberg, Andrew B.; Serruya, Mijail; Wintering, Nancy; Moss, Aleezé Sattar; Reibel, Diane; Monti, Daniel A.
Abstract : Neurodegenerative diseases pose a significant problem for the healthcare system, doctors, and patients. With an aging population, more and more individuals are developing neurodegenerative diseases and there are few treatment options at the present time. Meditation techniques present an interesting potential adjuvant treatment for patients with neurodegenerative diseases and have the advantage of being inexpensive, and easy to teach and perform. There is increasing research evidence to support the application of meditation techniques to help improve cognition and memory in patients with neurodegenerative diseases. This review discusses the current data on meditation, memory, and attention, and the potential applications of meditation techniques in patients with neurodegenerative diseases.